(untitled) (Research, Society and Development, 2021)
The determination and stipulation of appropriate limits with the principle of Contradictoire Delimitatie becomes the main keys before implementing the land measurement. Lawsuit could arise which results in re-measurement and even the cancellation of the certificate. This research is normative research type (doctrinal research), statute approach and conceptual approach and focuses to the literature study; the research source data is secondary data. The mechanism for determining and stipulation boundaries in land registration has applied the principle of safety. The law consequence if the determination and stipulation boundaries in land are not accordance with the fact in the field resulting in the absence of legal certainty for the certificate of land rights. Conclusion and suggestion in this research is in determination and determination of land plot boundaries in order to achieve legal certainty must in accordance with PP No. 24 of 1997 and PMNA/KaBPN No.3 (Regulation of the Minister of Agrarian and Spatial Planning/Head of BPN) of 1997. Magetan Regency National Land Agency Office before implementing the measurement activities must be thoroughly in the process of determination of land plot boundary in order to reaches the law certainty, it can be accounted for.